Computational mechanical characterisation of Schwarz P unit cell-based tissue scaffolds fabricated via two-photon polymerisation - Zabidi, Adi Zakwan (2019)
Schwarz P unit cell-based tissue scaffolds have been fabricated via two-photon polymerisation (2PP). In this thesis, a computational approach to characterising the mechanical properties of the scaffolds made of poly(D,L-lactide-co-ε-caprolactone)(PLCL) copolymer via micromechanical analysis is presented. The stereolithography (.STL) model of the Schwarz P unit cell design used as input for 2PP was ‘reverse engineered’ to obtain a surface geometry model for implementation in computational analyses. In the experimental model of this study, the mechanical properties of bulk material PLCL and fabricated tissue scaffolds were experimentally characterised. Data obtained from fabricated tissue scaffolds were used as a basis of comparison to data obtained from mechanical characterisation of the scaffold via computational analyses.